PENGARUH KEKAYAAN DAERAH, PENDAPATAN PERKAPITA, JUMLAH PENDUDUK, DAN TINGKAT PENDIDIKAN TERHADAP PUBLIKASI LAPORAN KEUANGAN PEMERINTAH DAERAH - Vivit Mariasari (Jurnal Akuntansi, 2023)
The management of the Local Government website as a means of realizing transparency and accountability in Indonesia has not been fully carried out optimally, where only about 49.58% of regency/city governments in Java island publish financial reports on the internet. This research aims to examine the factors that influence the desire of local governments to publish financial statements on the internet. The independent variables used in this study are Regional Wealth proxied by Total Assets, Per capita Income proxied by GRDP Per capita, Population Number, and Education Level proxied by the average length of schooling index. The object of research used in this study is the Regency/City Government in Java Island during the 2018-2021 period. The determination of samples in this study uses the puposive sampling method, which is the determination of samples using certain criteria. The number of samples in this study was 59 samples, out of 119 existing populations. The research method used in this study is the panel data regression analysis method. The panel data regression method was used because the data used in this study consisted of time series data and cross section data. The results showed that variables of regional wealth, population and level of education had a positive and significant influence on the publication of local government financial statements. Meanwhile, the variable per capita income does not have a significant influence on the publication of local government financial statements.